Ammonia-oxidizing microbial communities in reactors with efficient nitrification at low-dissolved oxygen. (1st March 2015) - Fitzgerald, Colin M.; Camejo, Pamela; Oshlag, J. Zachary; Noguera, Daniel R.
Abstract: Ammonia-oxidizing microbial communities involved in ammonia oxidation under low dissolved oxygen (DO) conditions (<0.3 mg/L) were investigated using chemostat reactors. One lab-scale reactor (NS_LowDO) was seeded with sludge from a full-scale wastewater treatment plant (WWTP) not adapted to low-DO nitrification, while a second reactor (JP_LowDO) was seeded with sludge from a full-scale WWTP already achieving low-DO nitrifiaction. The experimental evidence from quantitative PCR, rDNA tag pyrosequencing, and fluorescence in situ hybridization (FISH) suggested that ammonia-oxidizing bacteria (AOB) in the Nitrosomonas genus were responsible for low-DO nitrification in the NS_LowDO reactor, whereas in the JP_LowDO reactor nitrification was not associated with any known ammonia-oxidizing prokaryote. Neither reactor had a significant population of ammonia-oxidizing archaea (AOA) or anaerobic ammonium oxidation (anammox) organisms. Organisms isolated from JP_LowDO were capable of autotrophic and heterotrophic ammonia utilization, albeit without stoichiometric accumulation of nitrite or nitrate. Based on the experimental evidence we propose that Pseudomonas, Xanthomonadaceae, Rhodococcus, and Sphingomonas are involved in nitrification under low-DO conditions. Graphical abstract: Highlights: Reactors seeded with sludge from full-scale plants performing low-DO and high-DO nitrification. Ammonia-oxidizing archaea did not contribute to low-DO nitrification. Nitrification at low-DO in one reactor was not carried out by known ammonia-oxidizing prokaryotes. Our knowledge of the microbiology of low-DO nitrification remains incomplete. Pseudomonas, Xanthomonadaceae, Rhodococcus, Sphingomonas contribute to low-DO nitrification.